Facility-Level Variation in Hospitalization, Mortality, and Costs in the 30 Days After Percutaneous Coronary Intervention. Issue 2 (14th July 2015) - Bradley, Steven M.; O'Donnell, Colin I.; Grunwald, Gary K.; Liu, Chuan-Fen; Hebert, Paul L.; Maddox, Thomas M.; Jesse, Robert L.; Fihn, Stephan D.; Rumsfeld, John S.; Ho, P. Michael
<x xml:space="preserve">Abstract</x> Background— Policies to reduce unnecessary hospitalizations after percutaneous coronary intervention (PCI) are intended to improve healthcare value by reducing costs while maintaining patient outcomes. Whether facility-level hospitalization rates after PCI are associated with cost of care is unknown. Methods and Results— We studied 32 080 patients who received PCI at any 1 of 62 Veterans Affairs hospitals from 2008 to 2011. We identified facility outliers for 30-day risk-standardized hospitalization, mortality, and cost. Compared with the risk-standardized average, 2 hospitals (3.2%) had a lower-than-expected hospitalization rate, and 2 hospitals (3.2%) had a higher-than-expected hospitalization rate. We observed no statistically significant variation in facility-level risk-standardized mortality. The facility-level unadjusted median per patient 30-day total cost was $23 820 (interquartile range, $19 604–$29 958). Compared with the risk-standardized average, 17 hospitals (27.4%) had lower-than-expected costs, and 14 hospitals (22.6%) had higher-than-expected costs. At the facility level, the index PCI accounted for 83.1% of the total cost (range, 60.3%–92.2%), whereas hospitalization after PCI accounted for only 5.8% (range, 2.0%–12.7%) of the 30-day total cost. Facilities with higher hospitalization rates were not more expensive (Spearman ρ=0.16; 95% confidence interval, −0.09 to 0.39; P=0.21). Conclusions— In this national study, hospitalizations in the 30 day after PCI accounted for only 5.8% of 30-day cost, and facility-level cost was not correlated with hospitalization rates. This challenges the focus on reducing hospitalizations after PCI as an effective means of improving healthcare value. Opportunities remain to improve PCI value by reducing the variation in total cost of PCI without compromising patient outcomes.